Experiência do pensamento no ensino de filosofia no nível médio: entre Deleuze e a educação básica brasileira - Santos, Angelina Renata Andrade Ribeiro dos (2020)
The present research intends to investigate the theme referring to the experience of thinking in the teaching of philosophy at the high school level at Brazilian education. The thought experience investigated here is the understood we had according to Deleuze's philosophy (2013; 2018), and being part of the educational process, it is not in the beginning or the end, it is “between”. Considering this, we have as specific objectives to discuss the current conditions of teaching philosophy in Brazil with an emphasis on high school, to recognize the teaching of philosophy as a philosophical problem, to establish relationships between Deleuze's perspective and the experience of thinking at this level of education. In order to achieve these objectives, the path traveled by geophilosophy, a concept inspired by the authors Deleuze and Guattari (2010). As well as a cartographic of philosophical thought and philosophy teaching, the research has in its scope bibliographic procedure, in order that it contemplates aspects referring to the institutionalization of philosophy teaching in Brazil, having as its scenario its historical, legal and academic panorama; theoretical review of the problems of thought and philosophy in Deleuze from the works Difference and Repetition (2018) and What is philosophy? (2010), written in partnership with Guattari; ending with a discussion about the teaching of philosophy as a thought experience under the rule of the main categories found: concept, identity and difference. For that, we resort to analyzes about the paradoxes between learning and teaching philosophy, propositions arising from the pedagogy of the concept, and together another look at the notion of learning. We identified marked difficulties for the consolidation of the teaching of philosophy in Brazil, as well as significant contributions from Deleuze's perspective in academic production for the teaching of philosophy aimed at autonomous thinking, insofar as by drawing escape lines for teaching of philosophy (in difference), therefore, we have a teaching of philosophy as an experience of thought.